Optimization methods of the pavement management system of Budapest - Almassy, Kornel; Pusztai, Gábor; Gáspár, László; Lógó, János (Journal of Civil Engineering and Management, 2019)
A modern Pavement Management System (PMS) should be essential for maintenance a metropolitan urban road network. Municipality of Budapest has developed own management system for their road pavement operation. To an efficient outcome the newest methods are used for the data collecting with the most innovated geo-informatics solutions, which are help us in our multi criteria decision making process. We present a degradation model which useful for the prediction of the roughness, yielding surface condition of the pavement in the future. After the whole data evaluation we give accurate information about the general characterization of the permanent road network conditions. Our paper shows that in all modern asset management system based on multi criteria decision making processes, which contain single or multi objective optimization methods. The PMS based on the available-technical and financial data and its optimization process provides a pavement renovation offer for each road in Budapest transportation network and finally the paper presents how can we ranking the invention list from our optimization process.